2004
DOI: 10.1097/00126334-200405010-00012
|View full text |Cite
|
Sign up to set email alerts
|

Intersubtype BF Recombinants of HIV-1 in a Population of Injecting Drug Users in Argentina

Abstract: The presence of recombinant intersubtypes of HIV-1 in Argentina has been reported since the mid-1990s. In this study, sequences of a region of the gag, pol, and vpu genes of HIV-1 were analyzed in samples of 21 injection drug users (IDUs) residing in the suburbs of the city of Buenos Aires. Genomic characterization and identification of recombination sites were made comparing the 3 regions with reference isolation sequences of subtypes B, F, C, A, and B/F recombinants: CRF12_BF and non-CRF12_BF sequences. Subt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
1
1

Year Published

2004
2004
2011
2011

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 21 publications
1
23
1
1
Order By: Relevance
“…This area is a known drug traffic route from South American countries into Brazil, and intravenous drug use is an important exposure category in this area. Recent studies from South America have shown a link between B/F recombinants and extensive intravenous drug use (Hierholzer et al, 2002;Espinosa et al, 2004). Nevertheless, in Central West Brazil B/F isolates were observed in all risk categories.…”
Section: Discussionmentioning
confidence: 93%
“…This area is a known drug traffic route from South American countries into Brazil, and intravenous drug use is an important exposure category in this area. Recent studies from South America have shown a link between B/F recombinants and extensive intravenous drug use (Hierholzer et al, 2002;Espinosa et al, 2004). Nevertheless, in Central West Brazil B/F isolates were observed in all risk categories.…”
Section: Discussionmentioning
confidence: 93%
“…18 Estudos realizados na Argentina e Brasil mostraram que usuários de drogas injetáveis e mulheres apresentaram maior freqüência de recombinantes BF. 8,24 No RS, uma forma recombinante específi ca (CRF31_BC) tem apresentado prevalência bastante elevada, diferindo do restante do Brasil, e tem se disseminado no estado vizinho de Santa Catarina e em outros países limítrofes da América do Sul, tais como Uruguai, Paraguai e Argentina. 3,5 No Brasil estima-se que cerca de 506 mil pessoas estejam infectadas, das quais aproximadamente 46 mil estão no RS.…”
Section: Introductionunclassified
“…13 Another subtype B with V3 loop motif GPGRTW was recently described in Venezuela. 21 Brazilian subtype C (or C Br ) has as a characteristic tetramer GPGQ, 13 also found in Portugal, 36 Japan, 99 and India. 80 In relation to the subtype F, Brazilian F Br possesses GPGR motif 13 that has a small difference compared to the Romanian subtype F R with predominant GPGQ motif, occasionally also observed in Brazil.…”
Section: Intra-subtypesmentioning
confidence: 98%
“…18,54 In Argentina, Uruguay, and Brazil the CRF12_BF became prevalent in heterosexual population, and in vertically infected children. 17,36,51,114,116,120,121 In Brazil, the distribution of HIV-1 subtypes assumes diversified patterns according to the geographic regions. In the Brazilian Southern and Southeastern States the rate of subtype B arise to 50%, and subtypes C and F represent 28% and 7%, respectively, 127 while in Northeastern region occurs a high prevalence of B (>80%) followed by a low frequency (<3%) of subtype F and BC recombinant.…”
Section: Circulating Recombinant Formsmentioning
confidence: 99%
See 1 more Smart Citation